An overview of the poultry sector and status of Highly Pathogenic Avian Influenza (HPAI) in Kenya: Background paper - Omiti, John Moturi; Okuthe, Sam O. (International Food Policy Research Institute, 2009)
Poultry keeping in Kenya plays a major role as a livelihood source, an income generating activity as well meeting other socio-cultural roles. Poultry production is, however, threatened by the emerging HPAI threat that has devastated other parts of the world. This study documented available information on the poultry sector. The objective was to identify knowledge gaps that HPAI research in Kenya should focus on. A thorough review of existing literature was done including searches over the internet. The study found that Kenya had about 37 million birds in 2006 of which 84.1% were free-ranging indigenous birds, 8.4% were layers, 5.7% were broilers while other poultry species accounted for 1.8%. About 65% of Kenyan households keep chickens; each household keeps about 12 chickens on average. Poultry are produced in four main production systems, which are labelled Sectors 1 - 4 according to the FAO/OIE classification. Sector 1 consists of the integrated industrial producers (big companies), Sector 2 is made up of hatcheries, and Sector 3 is dominated by smallholder semi-commercial farmers while Sector 4 constitutes the village or "backyard" (traditional) poultry production system. The September 2005 HPAI scare is estimated to have caused a loss of about Ksh 2.3 billion (US$40,000) mainly due to reduced demand for poultry products as consumers shunned away these products. Prices of poultry and poultry products declined due to the scare. For instance, the price of one broiler, indigenous chicken and spent layer declined by 15%, 26% and 29% during the period of the HPAI scare. The price of indigenous eggs fell by 7% while that of the commercial eggs decreased by 15%. Significant gaps in knowledge still remain. Based on these findings, the study recommends the following: * There is a need to conduct a poultry population census (possibly together with that of other livestock species) in order to update and validate existing data. * There is a need to create awareness of HPAI among producers and consumers of poultry products in order to reduce their ignorance on the disease transmission and therefore avert possible losses due to a HPAI scare. * Compensatory mechanisms should be instituted, possibly through poultry insurance schemes, in order to cushion farmers and businesses in the poultry sector from economic losses associated with a HPAI outbreak or scare of an outbreak. * The veterinary department should come up with clear guidelines on the appropriate control approaches for the disease (e.g. to vaccinate or not vaccinate). Research is also needed in the following areas: * Evaluation of the poultry sector value chains to identify "hot spots" for HPAI entry to aid in designing effective control/eradication strategies; * Evaluation of different marketing channels of poultry and poultry products with a view to identifying key actors (who are they, how many, what are their incentives, how are they organized, etc) in those channels and their level of awareness of HPAI and its potential threat; * Evaluation of different segments of consumers with a view to promoting consumer awareness of HPAI risk; * Evaluation of the cost-effectiveness of alternative HPAI control strategies in the wake of a potential outbreak; * Appropriate compensation mechanisms that are suitable for the structure of the poultry sector in Kenya; * Potential losses arising from a disease outbreak or scare; * Risk analysis as a component of early warning system in risk based surveillance strategy; and * Impact of the disease and the control measures on the livelihoods of the poor.